2000
DOI: 10.1093/occmed/50.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Fitness and Body Composition of Finnish Police Officers: A 15-year Follow-up Study

Abstract: This study evaluated changes in the physical activity, fitness and body composition of 103 police officers during a 15-year follow-up. The absolute aerobic capacity was similar in 1981 and 1996, muscular performance had declined, and body weight had increased approximately 0.5 kg/year. More than half the subjects (53%) had increased their leisure-time physical activity in 1996. The correlation was significant between physical activity in 1981 and physical fitness in 1996, but weak between physical activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
3
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(179 citation statements)
references
References 10 publications
9
152
3
15
Order By: Relevance
“…Entre os danos psíquicos, pode-se apontar a dependência alcoólica, os abusos no uso de medicamentos, a depressão e os transtornos de diversos tipos, tais como a desordem de stress pós-traumático ou síndrome de exaustão emocional ou burn--out, entre outros (Loo, 2004). Já entre os danos físicos, podem ser citadas as doenças cardiovasculares e as doenças metabólicas, entre outras (Sorensen, Smolander, Louhevaara, Korhonen, & Oja, 2000 …”
unclassified
“…Entre os danos psíquicos, pode-se apontar a dependência alcoólica, os abusos no uso de medicamentos, a depressão e os transtornos de diversos tipos, tais como a desordem de stress pós-traumático ou síndrome de exaustão emocional ou burn--out, entre outros (Loo, 2004). Já entre os danos físicos, podem ser citadas as doenças cardiovasculares e as doenças metabólicas, entre outras (Sorensen, Smolander, Louhevaara, Korhonen, & Oja, 2000 …”
unclassified
“…Methodological quality of each study included in this review was also evaluated in an autonomous manner by 2 reviewers using an instrument developed by the authors and sometimes in conflict with maintenance of physical fitness [1,7,9,10]. Over the last decade, numerous studies on the changes in body composition of policemen caused by their occupation have been performed.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…With regard to the methods of obesity detection in the target population, direct measurements (body mass, fat mass, lean mass, abdominal girth, and waist circumference) as well as indirect measurements (body mass index, waist-height ratio, waist to hip ratio, and fat percentage) were used. The main demographic characteristics of the studies are shown in Table 1; 6 studies were performed in North America [6,7,[15][16][17]20], 2 in Europe [1,4], and 1 in South America [18]. Among the cohort studies, Boyce et al [4] studied both men and women, whereas Sorensen et al [1] included only men.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Policijski posao pripada kategoriji zanimanja kod kojih se višegodišnje dejstvo većeg broja faktora rizika može kumulativno i negativno odraziti na opšte zdravstveno i stanje profesionalno-radne sposobnosti (Bonneau & Brown, 1995;Sorensen et al 2000). Prvi stepen datog kumulativnog i negativnog uticaja radne sredine se može dijagnostikovati upravo pomoću morfološkog prostora, gde intenzitet i smer promena voluminoznosti tela, kao i telesnog statusa direktno ukazuje na dati uticaj (Janković i sar.…”
Section: Diskusijaunclassified